EFFECT OF NO-TILL PRECISE SEEDING ON WHEAT (TRITICUM AESTIVUM L.) POPULATION QUALITY AT THE EMERGENCE STAGE - T. Korohou; C. Okinda; H. Li; I. Torotwa; Q. Ding1; A. Abbas1. (Journal of Animal and Plant Sciences, 2022)
Sowing techniques and planting density directly affect the shape and microenvironment of the canopy and, therefore, the final yield. A field experiment was carried out during two consecutive years, 2017 and 2018, at Nanjing Agricultural University, Jiangsu Experimental Farm. The objective of the study was to compare the effect of the drill seeding and punch seeding of wheat at the emergence stage. The experiment comprised of three (1.5, 3.0 and 4.5 cm distances between seed) treatments arranged in randomized complete block design with three replications in a plot size of 4.0 by 5.0 m. During the two seasons of the experiment, a general tendency was observed for the two modes of sowing; the reduction of the growth parameters (the dry weight of the roots, the aerial biomass, and the number of roots) seedlings as the planting density increased. However, several parameters showed significant statistical variations, such as the emergence rate by age ratio of the seedlings, the dry weight of the biomass, the leaf area, the dry weight of the roots, the root volume, the length, the root depth, and root/soil ratio. The results showed that competition between plants began to appear at the stage of sowing, and the higher the planting density, the more the growth of the wheat population of individuals is hampered. Beyond the results, we have demonstrated the interest of characterizing the phenotypes of wheat through multiple criteria, also considering the whole plant at the emergence stage.
Keywords: Seeding; Single grain; Wheat seedling; Emergence stage; No-till